Financial liberalization and intervention : a new analysis of credit rationing - Basu, Santonu (Cheltenham, UK ; Northampton, MA : E. Elgar, 2002)
This text seeks to provide a coherent explanation as to why the policies of financial liberalization and financial intervention have been unable to achieve the goal of improving the access of borrowers to the loan market, irrespective of size.
Includes bibliographical references (p. 129-149) and index.
oif 21/07/16
Loans
Keywords: Credit control; Credit control; Credit control; Monetary policy; Monetary policy; Monetary policy